Altered Pharmacokinetics and Dosing of Liposomal Amphotericin B and Isavuconazole during Extracorporeal Membrane Oxygenation. Issue 1 (13th December 2019) - Zhao, Yanjun; Seelhammer, Troy G.; Barreto, Erin F.; Wilson, John W.
Abstract : Drug pharmacokinetics may be significantly altered in patients receiving extracorporeal membrane oxygenation (ECMO). Ensuring the optimized effective dosing of antimicrobials on ECMO remains a challenge. To date, limited data are available regarding the optimal use of amphotericin and triazoles during ECMO. We report a case of altered pharmacokinetics, insufficient liposomal amphotericin B and isavuconazole levels, and the need for escalated doses during ECMO in a patient with severe acute respiratory distress syndrome secondary to pulmonary blastomycosis. A 2‐fold increase in the standard total daily dose of both drugs was necessary to overcome low serum concentrations thought to be secondary to drug loss from ECMO circuit sequestration. These findings have important implications for optimizing antimicrobial therapy in patients receiving ECMO to maximize therapeutic efficacy. The use of therapeutic drug monitoring for patients receiving antimicrobial therapy with concurrent ECMO may facilitate appropriate drug dosing to achieve adequate serum concentrations and optimize favorable patient outcomes. Further studies exploring antimicrobial pharmacokinetics during ECMO are needed to inform dosing recommendations in critically ill patients.